Validation of the computed assessment of cleansing score with the Mirocam® system - Ana Ponte; Rolando Pinho; Adélia Rodrigues; Joana Silva; Jaime Rodrigues; João Carvalho (Revista Espanola de Enfermedades Digestivas)
Background and aims: A computed assessment of cleansing (CAC) score was developed to objectively evaluate small-bowel cleansing in the PillCam capsule endoscopy (CE) system and to overcome the subjectivity and complexity of previous scoring systems. Our study aimed to adapt the CAC score to the Mirocam® system, evaluate its reliability with the Mirocam® CE system and compare it with three validated subjective grading scales. Patients and methods: Thirty CE were prospectively and independently reviewed by two authors who classified the degree of small-bowel cleanliness according to a quantitative index, a qualitative evaluation and an overall adequacy assessment. The authors were blinded for the CAC score of each CE, which was calculated as ([mean intensity of the red channel]/[mean intensity of the green channel] - 1) x 10. The mean intensities of the red and green channels of the small-bowel segment of the "Map View" bar in the Miroview Client® were determined using the histogram option of two photo-editing software. Results: There was a strong agreement between both CE readers for each of the three subjective scales used. The reproducibility of the CAC score was excellent and identical results were obtained with the two photo-editing software. Regarding the comparison between the CAC score and the subjective scales, there was a moderate-to-good agreement with the quantitative index, qualitative evaluation and overall adequacy assessment. Conclusions: CAC score represents an objective and feasible score in the assessment of small-bowel cleansing in the Mirocam® CE system, and could be used per se or as part of a more comprehensive score.